2007
DOI: 10.1063/1.2751168
|View full text |Cite
|
Sign up to set email alerts
|

On the thermodynamic stability of hydrogen clathrate hydrates

Abstract: The cage occupancy of hydrogen clathrate hydrate has been examined by grand canonical Monte Carlo ͑GCMC͒ simulations for wide ranges of temperature and pressure. The simulations are carried out with a fixed number of water molecules and a fixed chemical potential of the guest species so that hydrogen molecules can be created or annihilated in the clathrate. Two types of the GCMC simulations are performed; in one the volume of the clathrate is fixed and in the other it is allowed to adjust itself under a preset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 18 publications
7
51
0
3
Order By: Relevance
“…Additional studies that consider the case of multiple occupancy include, among others, the experimental [24][25][26] and the theoretical [27][28][29] works for nitrogen, the experimental [30,31] and the theoretical [32][33][34][35][36][37] works for hydrogen, and the theoretical work for carbon dioxide [38].…”
mentioning
confidence: 99%
“…Additional studies that consider the case of multiple occupancy include, among others, the experimental [24][25][26] and the theoretical [27][28][29] works for nitrogen, the experimental [30,31] and the theoretical [32][33][34][35][36][37] works for hydrogen, and the theoretical work for carbon dioxide [38].…”
mentioning
confidence: 99%
“…Katsumasa et al [46] examined the cage occupancy of hydrogen clathrate hydrates using grand canonical Monte Carlo (GCMC) simulations for wide ranges of temperature and hydrogen pressures. Their simulations were carried out with a fixed number of water molecules and a fixed chemical potential for the guest hydrogen molecules.…”
Section: Modeling Of Hydrogen Clathrate Hydratesmentioning
confidence: 99%
“…Lee et al [6] reported a H 2 -storage capacity around 4 wt% at 12 MPa and 270 K, and the composition of the clathrate hydrates was tuned to optimize gas-storage capacity, [6,7] although subsequent studies suggest lower storage capacities under similar conditions. [8][9][10][11] Other clathrates capable of retaining a significant amount of H 2 at moderate pressures and temperatures are being investigated. [12][13][14][15] The extremely slow kinetics of H 2 encapsulation into clathrate hydrate cages, [6,8,16,17] resulting from mass diffusion in a bulk solid phase, may be a generic limitation for the applicability of clathrates in the storage of H 2 and other gases.…”
mentioning
confidence: 99%
“…Previous studies have measured H 2 capacity in hydrates indirectly using Raman or NMR spectroscopy conducted at low temperatures, and this can lead to discrepancies [6,8,9] in the reported H 2 capacities since these are closely related to factors such as temperature, pressure, composition, and kinetic conditions. [11,23] In this work, volumetric release experiments [8,20] were carried out to further confirm the H 2 capacity as calculated from the observed pressure drop. The amount of H 2 evolved in each case was consistent with the calculated H 2 enclathrated in Figure 2a.…”
mentioning
confidence: 99%